Production of abe (acetone-butanol-ethanol) from pome by clostridium beijerinckii - Nur Akmalina, Azeman (2013)
Malaysia was one of the biggest producers and exporters of palm oil and palm oil products (Malaysian Palm Oil Council, 2012). Thus, the total oil palm cover has increased with a corresponding increase in palm oil production. As a result, palm oil waste which was a by-product of the milling process will also increase. Due to the presence of high total solids in palm oil mill effluent (POME), attempts have been made to convert this waste into valuable products such as feed stock (Rupani et al., 2010). Consequently, purpose of this research was to study about the production of acetone-butanol-ethanol (ABE) solvents using POME by Clostridia beijerinckii. These ABE solvents which are consist of acetone, butanol and ethanol have each one benefits such as butanol used for biofuel, acetone used for making plastic and ethanol can be used as disinfectant. The culture was grown in RCA and then 10% v/v of the culture was transferred to RCM for preparation of inoculum medium. After that, 10% v/v of inoculum medium was transferred into fermentation medium which consists of 90% of POME. In this research, POME would be used as substrate medium. Then, the fermentation medium was run to find the optimum pH for fermentation medium (initial pH 5.4 until 6.2), concentration of POME (80% to 100% v/v) and temperature of fermentation (27°C to 47°C). The highest value of total ABE obtained was 0.771 g/L with 90% concentration at condition of pH 5.8 of 37°C.